Professional Development Of Teaching Staff In The Process Of Advanced Training As A Scientific And Pedagogical Problem (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article examines the issues of professional development of teaching staff in the process of advanced training as a scientific and pedagogical problem. Systemic and innovative approaches to advanced training of teachers, as well as issues of improving the educational process using information and communication technologies are analyzed. Based on the analysis of scientific works of scientists of our republic on the development of professional competence of teachers, problems and prospects of the advanced training process are identified.